Wadsworth-emmons reaction by using the fluorapatite catalyst: kinetic studies - Vishwakarma, Rakhi; Vinod, Chathakudath P.; Rathod, Virendra; Kantam, Mannepalli Lakshmi (Industrial & Engineering Chemistry Research, 2023)
Wadsworth-Emmons reaction was successfully carriedout byusing the fluorapatite (FAP) catalyst. The reaction of 2-methoxybenzaldehydeand triethylphosphonoacetate using FAP afforded & alpha;,& beta;-unsaturatedester with 100% conversion and 80% selectivity. A kinetic model wasvalidated at different temperatures by Langmuir-Hinshelwood-Hougen-Watson(LHHW), and the absence of mass transfer resistance was verified bythe Weisz Prater criterion. The effect of different catalysts, temperature,catalyst loading, solvent, mole ratio, and speed of stirring was studied.The FAP catalyst was characterized by Fourier transform infrared spectroscopy,Brunauer-Emmett-Teller method, nitrogen adsorption-desorption,transmission electron microscopy, energy-dispersive X-ray spectroscopy,temperature programmed desorption (TPD-NH3), X-ray diffraction,and X-ray photoelectron spectroscopy. The FAP catalyst was found tobe stable up to three recycles with no loss in activity.